Electrochemical Preparation, Redox Behaviour and Stability of Some Electroactive Films Having Organic/ Organic and Organic/Inorganic Hybrid Structures - CHOWDHURY, AL-NAKIB; AKTER, MOSHARREFA (Asian Journal of Chemistry, 2010)
Electrochemical polymerization of aniline from the electrolytic solutions containing (i) organic dyes, viz., methylene blue or procion red and (ii) inorganic oxide, TiO2 leads to the formation of stand-alone electroactive polyaniline/methylene blue, polyaniline/procion red and polyaniline/TiO2 composite films, respectively. The presence of methylene blue, procion red and TiO2 significantly affects the rate of formation, morphology and the redox activity of the composite films. The electrochemical stability of the film at highly positive potential was also examined. The results based on cyclic voltammograms demonstrate that although overoxidative degradation takes place with the composite films, the extent of degradation is not as drastic as happened with the bulk polymer film suggesting a better electrochemical stability of the composite film relative to the bulk polyaniline one.